EFFECTIVENESS OF HERBAL AND CONVENTIONAL MANAGEMENT INTERVENTIONS OF HEPATITIS B VIRUS - ADEBAYO , Julius John; IBRAHEEM , Lawal Odula; OMORUYI , Beauty Etinosa; OKUDOH , Vincent Ifeanyi (African Journal of Infectious Diseases (AJID), 2024)
Background: Liver inflammation caused by the Hepatitis B virus (HBV) could become chronic and unresolved if untreated. Prevention and management of the disease are through vaccination and other conventional interventions. This study evaluated the cost-effectiveness of herbal management (HM) and conventional pharmaceutical management (PM) interventions in treating HBV. Materials and Methods: A purposive sampling technique was used to administer questionnaires at the University College Hospital (UCH) and Total Healthcare Diagnostic Centre (THDC). Data collection was according to a EuroQol (EQ -5D), while descriptive and inferential analyses were performed. Results: Findings revealed a high prevalence of HBV among females from ages 26 to 50. The majority discovered their health status through free HBV tests. Other than cost-effective interventions, about 73% of cases adopted HM to manage the disease. A significant difference (P<0.00) was observed in the correlation analysis of the current health status of respondents and the intervention management adopted. correlation analysis of the current health status of respondents was significantly different (P<0.01) against the intervention management adopted (P<0.00). Conclusion: The minister of health should emphasize HBV regular screening, subsidized viral load test and free vaccination in both public and private healthcare centres.